Considerations in Design of Interior Spaces for Autistic Children - Shareef, Sardar Sulaiman (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Autism nowadays has become one of the most prominent neurological disorders around the world. Despite having many medical and psychological endeavors and educational programs autism rate is increasing annually. Autism is a neurological disorder that is why finding a definite treatment seems to be difficult. Furthermore, especially in developing countries there is a lack of information about autism and how to behave with autistics, for that, many autistics get no education and do not have a chance to communicate with other people. This creates social, economic, and psychological problems in society. From 2000s onwards there are few attempts to search about autistics’ needs in physical environment pertaining to architectural design. However, the disorder requires more research and observation to know which spatial qualities may enhance their performance in learning process, and encourage them to participate in the normal life. The Purpose of this study is to prepare a comprehensible design checklist for architects and interior designers to be used in design of spaces for autistics. The study focuses on children with autism at age 3-7 years while they are in preschools and kindergartens and preparing to go to primary schools. The design checklist is prepared based on the data obtained from literature survey as well as the information gained from the experts as psychologists, sociologists, and therapists who worked in autism centers and parents and siblings of autistics who answered the questionnaires. For that reason, two autism centers were chosen in Iraqi-Kurdistan as case studies. The result of this research is a collection of findings related to autistics’ sensitivities in space, related to their seven senses. More interpretations have been done to translate this information to find what makes autistics comfortable to be used in spaces and what makes them distracted to be avoided in the physical environment. This research highly recommends this design checklist to architects and interior designers who intend to design spaces for autistics, as it includes many design considerations for autistics based on a scholarly research. Keywords: Autism, sensitivity in autism, universal design, senses of space, autism and interior space.

ÖZ: Günümüzde Otizm dünyadaki en önemli nörolojik düzensizlikler arasında yer almaktadır. Tıp ve psikolojik alanda gerçekleşen birçok girişim ve eğitsel programa rağmen otizm hala hızlı bir şekilde yayılmaktadır. Otizm nörolojik bir düzensizlik olduğundan ona kesin bir tedavi bulmak zor görünmektedir. Ayrıca, özellikle de gelişen ülkelerde otizm ve otistik insanlarla nasıl davranılması gerektiği hakkında bilgi eksiktir; bu nedenle birçok otistik insan eğitim alamıyor ve diğer insanlarla iletişim kurma şansı olamıyor. Bu da toplumda sosyal, ekonomik ve psikolojik problemlere yol açar. 2000’li yıllardan başlayarak mimarlık tasarımla ilişkin otistiklerin çevrede ihtiyaçları ile ilgili birkaç araştırma girişimi gerçekleşmiştir. Ancak, hangi mekânsal nitelikleri otistiklerin öğrenme sürecini ve onların normal hayata katılımlarını geliştirebileceği konusunda daha fazla araştırma ve gözleme gereksinim vardır. Bu çalışmanın amacı, otistikler için mekân tasarımında kullanılmak üzere mimarlar ve iç mimarlar için kapsamlı bir rehber hazırlamaktır. Çalışma 3-7 yaş arası kreş ve ana okulda olan ve ilkokula gitmeye hazırlanan otistik çocuklara odaklanmaktadır. Bu rehber, literatür taramasından ve otistik çocuklarla çalışan psikologlar, sosyologlar, ve terapistler gibi uzmanlar ve otistik çocukların aileleri ile yapılan anket sonucunda oluşan verilere dayanarak oluşturulmuştur. Bu nedenle Irak Kürdistan bölgesinde iki otizm merkezi araştırma alanı olarak seçilmiştir. Bu araştırmanın sonucunda hem çok duyarlı, hem az duyarlı otistik bireylerin yedi duyusuna bağlı olarak oluşan mekânsal ögelere karşı hassasiyetleri ile ilgili veriler toplanmıştır. Bu veriler fiziki çevrelerde otistikleri rahatlatmak için kullanılması gereken ve onların dikkatini dağıtan ve mekânda kaçınılması gereken ögeleri bulmak üzere yorumlanmıştır. Araştırma, otistikler için mekân tasarlamaya niyetlenen mimarlar ve iç mimarlara bilimsel araştırmaya dayalı ve otistikler için mekân tasarımında dikkate alınması gereken birçok hususu barındıran kapsamlı bir tasarım rehberi sunmaktadır. Anahtar kelimeler: Otizm, otizmde duyarlılık, evrensel tasarım, mekân algısı, otizm ve iç mekân
Master of Science in Interior Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2016. Supervisor: Assist. Prof. Dr. Guita Farivarsadri.
Keywords: Interior Architecture; Children's rooms-Interior Design; Architecture and children; Autism; sensitivity in autism; universal design; senses of space; autism and interior space